Comparative effects of microtubules disruption on glucocorticoid receptor functions in proliferating and quiescent cells - Vrzal, Radim; Gerbal-Chaloin, Sabine; Maurel, Patrick; Dvorák, Zdenĕk (International journal of toxicology, 2010)
We have recently demonstrated that the alkaloid colchicine (COL) inhibits glucocorticoid receptor (GR) transcriptional activity. In addition, we described proteasome-mediated degradation of GR in COL-treated HeLa cells. While these effects were previously attributed to cell cycle arrest in G2/M phase, this explanation is not applicable for nonproliferating cells such as human hepatocytes (HH). In the current study, we compared COL-mediated microtubule disruption and cell cycle arrest with selected GR functions in HeLa cells and HH as models of proliferating and quiescent cells, respectively. Microtubule disruption led to irreversible decrease in GR binding capacity and protein level in HeLa cells. None of the parameters was restored 24 hours after COL withdrawal. In contrast, dexamethasone (DEX) binding was increased in HH at the beginning of the treatment, with following transient activation of extracellular signal-regulated kinase (ERK). The findings of these investigations emphasize the GR-signaling differences between primary and transformed cells.
Keywords: hepatocyty; aktivace enzymů; HeLa Cells; Receptors, Glucocorticoid; proliferace buněk; Microscopy, Fluorescence; kolchicin; mikrotubuly; průtoková cytometrie; Enzyme Activation; receptory glukokortikoidů; Colchicine; Cell Cycle; Time Factors; časové faktory; lidé; HeLa buňky; Flow Cytometry; signální transdukce; fluorescenční mikroskopie; Signal Transduction; Hepatocytes; Ligands; buněčný cyklus; Humans; Tubulin Modulators; dexamethason; Dexamethasone; Cell Proliferation; modulátory tubulinu; Microtubules; extracelulárním signálem regulované MAP kinasy; ligandy; Extracellular Signal-Regulated MAP Kinases